A Multinational Observational Study Exploring Adherence With the Kidney Disease: Improving Global Outcomes Recommendations for Prevention of Acute Kidney Injury After Cardiac Surgery. (April 2020) - Küllmar, Mira; Weiß, Raphael; Ostermann, Marlies; Campos, Sara; Grau Novellas, Neus; Thomson, Gary; Haffner, Michael; Arndt, Christian; Wulf, Hinnerk; Irqsusi, Marc; Monaco, Fabrizio; Di Prima, Ambra Licia; et al.
Abstract : BACKGROUND: The Kidney Disease: Improving Global Outcomes (KDIGO) guidelines recommend a bundle of different measures for patients at increased risk of acute kidney injury (AKI). Prospective, single-center, randomized controlled trials (RCTs) have shown that management in accordance with the KDIGO recommendations was associated with a significant reduction in the incidence of postoperative AKI in high-risk patients. However, compliance with the KDIGO bundle in routine clinical practice is unknown. METHODS: This observational prevalence study was performed in conjunction with a prospective RCT investigating the role of the KDIGO bundle in high-risk patients undergoing cardiac surgery. A 2-day observational prevalence study was performed in all participating centers before the RCT to explore routine clinical practice. The participating hospitals provided the following data: demographics and surgical characteristics, AKI rates, and compliance rates with the individual components of the bundle. RESULTS: Ninety-five patients were enrolled in 12 participating hospitals. The incidence of AKI within 72 hours after cardiac surgery was 24.2%. In 5.3% of all patients, clinical management was fully compliant with all 6 components of the bundle. Nephrotoxic drugs were discontinued in 52.6% of patients, volume optimization was performed in 70.5%, 52.6% of the patients underwent functional hemodynamic monitoring, close monitoring of serum creatinine and urine output was undertaken in 24.2% of patients, hyperglycemia was avoided in 41.1% of patients, and no patient received radiocontrast agents. The patients received on average 3.4 (standard deviation [SD] ±1.1) of 6 supportive measures as recommended by the KDIGO guidelines. There was no significant difference in the number of applied measures between AKI and non-AKI patients (3.2 [SD ±1.1] vs 3.5 [SD ±1.1]; P = .347). CONCLUSIONS: In patients after cardiac surgery, compliance with the KDIGO recommendations was low in routine clinical practice.